Forbidden love - McCarthy, John.; Coughlan, Rachel; British Broadcasting Corporation (London : British Broadcasting Corporation, 1998)
For many Asian women arranged marriages are successful. But those who reject tradition can face violence, intimidation and isolation. For them, falling in love with the wrong person can be quite literally fatal. Three mixed race couples whose lives have been shattered talk to Inside Story about the high price of their love.
Title from resource description page (viewed May 9, 2014).
This edition in English.
Keywords: Marriage; Free love; Mariage; Amour libre; Free love; Marriage; Documentary films; Documentary films; Documentaires